Duplex Ultrasound Scan Can Prevent Leg Amputation in Severe Postthrombotic Syndrome: A Case Report - Chien Lin Soh; Carlos Pinho; Manal Ahmad; Alun H. Davies (Case Reports in Vascular Medicine)
Conclusion: Duplex provided vital information for surgical planning, which venogram was unable to offer. This is an imaging pitfall that is important to be aware of in patients presenting with recurrent venous disease. Our case highlights the importance of thorough clinical assessment and the value of the Doppler ultrasonography assessment in confirming venous incompetence.